The Influence of Cross-Selling Marketing and Service Quality on the Decision to Use Murabahah Financing Products with Member Trust as a Moderating Variable - Himmah Mazro'atul; Nur Huda; Irma Istiariani (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - This study aims to analyze the influence of cross-selling marketing and service quality on the decision to use murabahah financing products with member trust as a moderating variable at KSPPS Nusa Ummat Sejahtera KC Sudirman, Semarang City. Method - This study used a quantitative approach, collecting data through questionnaires distributed to members using murabahah financing products at KSPPS Nusa Ummat Sejahtera KC Sudirman. Data analysis was conducted using multiple regression and moderated regression analysis to test the proposed hypothesis. Result - The results of the study indicate that cross-selling marketing and service quality have a positive and significant influence on the decision to use murabahah financing products. The results of the study using moderated regression analysis showed that cross-selling marketing had a negative and significant influence, service quality had a positive and significant influence, trust had a positive and significant influence and strengthened cross-selling marketing relationships, trust had a negative and significant influence and weakened service quality on the decision to use murabahah financing products. Implication - This study identifies the use of murabahah financing products at KSPPS Nusa UMmat Sejahtera KC Sudirman, Semarang City. Originality - The originality of this research lies in its specific focus, namely the Sharia Savings and Loans and Financing Cooperative (KSPPS) as the object of research and also highlights the important role of member trust as a moderating variable between cross-selling marketing, service quality and Murabahah financing decisions. Keywords: Cross Selling Marketing, Service Quality, Trust, Murabahah Financing, Savings and Loan Cooperatives, Sharia Financing.